The Analysis of Factors Related to Anemia Levels in Adolescent Girls - Romadhon, Wimar Anugrah; Kartika Sari, Yeni; Putri, Raden Roro Dewi Rahmawaty Aktyani; Dwi Novitasari, Adelia (STIKes Patria Husada Blitar, 2024)
The impact on teenagers, if they experience anemia, is that it disrupts their ability to learn, reduces their physical exercise ability and body fitness, reduces individual work capacity, reduces the body's immune function, and reduces the ability to regulate body temperature. This research aimed to analyze factors related to anemia in adolescent girls. The research method used quantitative with a cross-sectional approach. The population in the study were all 50 Adolescents who were checked for Hb in March and had moderate anemia. The sample was 44 respondents taken by purposive sampling technique. The instrument used a questionnaire to determine the length of the menstrual period, nutritional status, knowledge, and iron intake. The research used an ordinal distribution used an ordinal regression test. The research results showed that the variable length of menstruation was 0.879 with p=0.348 (> 0.05), the nutritional status variable was 0.231 with p=0.631 (>0.05), the knowledge level variable was 4.407 with p=0.021 (>0.05) and the nutritional intake variable was 11.575 with p=0.001 (<0.05). This meant that the level of knowledge and nutritional intake was related to the level of anemia. Meanwhile, the length of menstruation and nutritional status were not related to the level of anemia. For future researchers, it is expected to provide interventions related to knowledge including individual or group counseling as well as providing a healthy lunch menu program to increase iron intake in adolescents.